The nexus between economic growth, institutional quality, and poverty in Nigeria / Adebowale Mojeed Olawale ... [et al.] - Olawale, Adebowale Mojeed; Kehinde, Joseph Elizabeth; Lola, Gold Kfilah; Agboola, Yusuf Hammed; Adebayo, Ojuolape Muhammed; Modupe, Ogunleye (Universiti Teknologi MARA Selangor, 2023)
Poverty, institutional quality, and economic growth are all crucial to a country's development and have garnered attention from scholars and policymakers over the years. This study looked at the relationship between poverty, institutional quality, and economic growth in Nigeria from 1996 to 2018, applying the techniques of Fully Modified OLS (FMOLS) and Causality test. The two institutional quality variables that were used are rule of law and corruption control. Consequently, the study established that an increase in control of corruption (a corruptionfree environment), GDP growth, government expenditure, and gross capital formation had reducing effects on poverty in the short run. Also, control of corruption had a negative effect on relative poverty, indicating that a corrupt free environment limits the spread of poverty in the country. Hence, it was recommended, amongst others to encourage people to do the right thing and prioritise basic human values such as honesty and integrity. Therefore, the government is advised to embark on mind orientation, especially in primary and secondary school, in order to build the future of the nation from the ground. Also, the administration and implementation of the rule of law and the judicial system of the nation should be revisited with the intention of causing them ( the law, the judicial system, and the institution governing the land) to favor the rights and good of the people..